NiFe Hydroxide Lattice Tensile Strain: Enhancement of Adsorption of Oxygenated Intermediates for Efficient Water Oxidation Catalysis. (17th December 2018) - Zhou, Daojin; Wang, Shiyuan; Jia, Yin; Xiong, Xuya; Yang, Hongbin; Liu, Song; Tang, Jialun; Zhang, Junming; Liu, Dong; Zheng, Lirong; Kuang, Yun; Sun, Xiaoming; et al.
Abstract: The binding strength of reactive intermediates with catalytically active sites plays a crucial role in governing catalytic performance of electrocatalysts. NiFe hydroxide offers efficient oxygen evolution reaction (OER) catalysis in alkaline electrolyte, however weak binding of oxygenated intermediates on NiFe hydroxide still badly limits its catalytic activity. Now, a facile ball‐milling method was developed to enhance binding strength of NiFe hydroxide to oxygenated intermediates via generating tensile strain, which reduced the anti‐bonding filling states in the d orbital and thus facilitated oxygenated intermediates adsorption. The NiFe hydroxide with tensile strain increasing after ball‐milling exhibits an OER onset potential as low as 1.44 V (vs. reversible hydrogen electrode) and requires only a 270 mV overpotential to reach a water oxidation current density of 10 mA cm −2 .